Domestic Rainwater Harvesting in a Water-Stressed Community and Variation in Rainwater Quality from Source to Storage - Owusu-Boateng, G.; Gadogbe, M. K. (Consilience, 2015)
The quality of rainwater, which is the main source of domestic water in Dzodze, a community in the Volta Region of Ghana, was unknown. Therefore, the possible utilization of contaminated domestic water and occurrence of health hazards could not be underestimated due to prevailing poor hygiene and a great lack of standard maintenance and treatment systems in the community. In this study, we assessed the quality of rainwater in the Dzodze Community community and how it varies along the DRWH[BH1] chain from free-fall to storage. Rain samples were collected at three points along the domestic rainwater harvesting (DRWH) chain. Specifically, the three points from were free-fall, roof-catchmentroof catchment, and storage tank, and the two systems were “described as poorly-maintained” and “well-maintained” systems. The physico-chemical and bacteriological patterns of rainwater samples were analyzed for physico-chemical and bacteriological parameters and results were compared with World Health Organization (and Ghana Standards Board guideline values. The harvested rainwater was found to be of good physico-chemical quality, but not bacteriological, quality but not bacteriological, calling for treatment before utilization. Also, irrespective of the type of DRWH system (poorly-maintained or well-maintained), there were substantial changes in rainwater quality upon interaction with roof-catchmentroof catchment, with an increase noticed in all parameters.